2018
DOI: 10.1016/j.ensci.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral microbleeds and blood pressure abnormalities in Parkinson's disease

Abstract: Blood pressure abnormalities are frequently observed in patients with Parkinson's disease (PD), and are associated with cerebrovascular diseases such as white matter hyperintensities and carotid atherosclerosis. We assessed the relationship between blood pressure abnormalities and cerebral microbleeds (CMBs), a marker of cerebral small vessel disease, in 128 patients with PD. We examined supine and orthostatic blood pressures and used 24-hour ambulatory blood pressure monitoring to assess the presence or absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…Anatomical analysis has revealed that deep CMB is more prevalent than lobar CMB. People with a history of hypertension and stroke are more likely to have CMBs, and the presence of deep or infratentorial CMB is associated with orthostatic hypotension and supine hypertension [15][16][17][18][19][20][21]. The present study demonstrated a higher prevalence of CMB in Taiwanese people with early-and mid-stage PD compared with previous studies, which may partially have resulted from the greater proportion of people with stroke history in the present study compared with those in other studies.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Anatomical analysis has revealed that deep CMB is more prevalent than lobar CMB. People with a history of hypertension and stroke are more likely to have CMBs, and the presence of deep or infratentorial CMB is associated with orthostatic hypotension and supine hypertension [15][16][17][18][19][20][21]. The present study demonstrated a higher prevalence of CMB in Taiwanese people with early-and mid-stage PD compared with previous studies, which may partially have resulted from the greater proportion of people with stroke history in the present study compared with those in other studies.…”
Section: Discussioncontrasting
confidence: 55%
“…Approximately 15-20% of people with PD present CMBs [15][16][17][18][19][20][21]. In addition, the presence of a deep or infratentorial CMB is associated with hypertension, orthostatic hypotension, and a history of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…It is curious that no subanalysis of PD patients with HBP was performed, therefore there is no available data regarding the interaction between HBP and OH in PD patients. In two studies, PD patients with OH had a slightly lower prevalence of HBP compared to non-OH patients (33.3% in OH vs. 49.2% in non-OH, p = 0.19; 21.7% in OH vs. 26.5% in non-OH, p = 0.53) [ 19 , 25 ], in other two studies there were opposite results (42.86% in OH vs. 38.61% in non-OH, p = 0.61; 38% in OH vs. 20% in non-OH, p = 0.04) [ 20 , 21 ], whereas another one reported equal prevalence of HBP among the two groups ( p = 1) [ 28 ], which makes it difficult to draw conclusions regarding the association between HBP and OH. In one study, a group of 26 patients with untreated HBP without PD served as control group for PD patients without HBP, revealing higher left ventricular mass (indexed to body surface) in both HBP and reverse dipper PD compared to non-reverse dipper PD patients [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study found that in patients with early PD and SH the motor symptoms and cognitive decline seemed to be worse compared to non-SH patients [ 42 ]. Moreover, SH was significantly correlated with restless legs syndrome [ 38 ], carotid artery thickening [ 37 ]/arterial stiffness [ 28 ] and an increased number of cerebral microbleeds in any brain region [ 25 ]. SH during sleep was shown to lead to NH, classified in 737 patients in our studies (38.91% of the patients investigated for NH).…”
Section: Resultsmentioning
confidence: 99%
“…SH is often companied by OH in neurodegenerative disorders with autonomic dysfunction [ 19 ], and the neurogenic OH group showed a significantly higher prevalence of SH than no-OH and non-neurogenic OH in our cohort. Because CMBs are more abundant in cases of OH accompanied by SH than in OH without SH among PD patients [ 28 ], SH rather than OH may increase the susceptibility of end-organ damage and small vessel disease related to cognitive impairment in PD.…”
Section: Discussionmentioning
confidence: 99%